2021
DOI: 10.1016/j.apmr.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Pressure Injuries on Admission to Inpatient Rehabilitation Hospitals During the COVID-19 Pandemic

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Ultimately, 19 publications were included (Figure 2). 1,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 19 publications were included (Figure 2). 1,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Resultsmentioning
confidence: 99%
“…During the first wave of COVID-19, COVID-19 patients tend to present a higher number of acute wounds, mainly of hospital origin, than the non-COVID group profile [ 24 ]. Prevalence of PIs on admission during the COVID-19 pandemic in the study by Kendall et al [ 28 ] was increased when compared with the pre-COVID-19 period by 14.9%. There was no difference in the prevalence of PIs in the COVID-19 period between patients who were COVID-19-positive and COVID-19-negative (35.4% vs 35.7%).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study demonstrated that PI severity worsened during the COVID period. 38 By contrast, a multicenter retrospective cohort demonstrated that patients with hip fractures during the pandemic had low Charlson comorbidity index and American Society of Anesthesiologists scores. 39 In addition, Lim et al 40 reported that patients with out‐of‐hospital cardiac arrest had a reduced admission survival rate and discharge survival rate and less favourable neurological outcomes during the COVID period.…”
Section: Discussionmentioning
confidence: 96%
“…These changes may have catastrophic consequences for patients with PIs and negative effects in many other aspects. A retrospective study demonstrated that PI severity worsened during the COVID period 38 . By contrast, a multicenter retrospective cohort demonstrated that patients with hip fractures during the pandemic had low Charlson comorbidity index and American Society of Anesthesiologists scores 39 .…”
Section: Discussionmentioning
confidence: 99%